The Educational Video "Dental Trauma to Primary Teeth” Increases the Awareness of Early Childhood Education School Teachers : An Experimental Study - Fauziah, Eva; Kusumaningrum, Astri; Khairani, Annisa; Widyagarini, Amrita (Padjadjaran Journal of Dentistry, 2023)
ABSTRACT Introduction: Dental trauma of primary teeth is more common in boys than in girls, and it frequently affects maxillary anterior primary teeth. Approximately 25% of schoolchildren worldwide have had dental trauma, although its prevalence varies among different countries. Group education through public lectures, television, community posters, leaflets, or videos can be selected as an educational method. The ineffective management of trauma to primary teeth is related to a lack of awareness among parents, schoolteachers, and health workers. Dental trauma mostly happens when children are at school; therefore, the study was conducted on Early Childhood Education (ECE) teachers' awareness before and after watching educational video "Dental Traumato Primary Teeth". The aim of this study is to determine the influence of the video "Dental Trauma to Primary Teeth” on ECE teachers’ awareness. Methods: This study used an experimental study approach by involving sixty-four ECE school teachers in Jakarta. They watched educational video "Dental Trauma to Primary Teeth" for two minutes before spending ten minutes answering questions to evaluate their understanding of dental trauma in children before and after viewing the film. The questionnaire was divided into 2 parts: the first part consisted of questions about sex, age, and education, and the second part consisted of nine questions about dental traumato primary teeth. The data were analyzed by comparing understanding before and after watching the educational video. Results: This research showed that all questions were answered correctly. There was an increasing percentage (1.5%-15.6%) after giving the video. The difference between the teacher's degree of awareness before and after watching educational video "Dental Trauma to Primary Teeth" was statistically significant (p ≤ 0.05). Conclusion: Providing children with educational media in the form of a video titled “Dental Trauma to Primary Teeth” is effective and can increase ECE teachers’ awareness of trauma to primary teeth.